(3GdLegQI aj GdHjRQIs - (3YjSi Hf Ydj MSGf GdGSOjs ((3YHO QHg Hf eMeO Hf CMeO Hf YHO GdQMef Hf Ydi GdTYQGfi GdCfUGQi s)
(3ChdgG (B:s
(3JHOC HfgGAI GdebOeI hagQSJ CHhGH GdLRA GdChd HHGH GdchGajf hZjQge heG jfHZi Cf jaYd cd CMO s
(3BNQgG (B:s
(3HGH GdMbfI HYO Cf CfgjJ LejY CHhGH GdcJGH ef CQGO Cf jJUjO TjFkG ef WjhQ GdHQjI cGdLQM hGdMHGQ hGdcQhGf hGdMLd hGdSeGf heG TGcd Pdc cdg e gPg GdCLfGS GfJgi GdLRA GdKGfi hHfgGjJg ced GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs